(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Urbanization has been on the rise in India since the country's independence. Numerous changes have taken place in the governance, social climate, economic structure, etc. The most noticeable aspect is that existing urban centers are growing in size due to invasion, or they have a significant impact on the cultural practices and way of life of the local rural population. great connectivity, sufficient amenities, and improved opportunities are all proven to contribute to a great quality of life. The degree of insight and awareness, however, determines quality of life more often than connectivity, facilities, opportunities, etc. A higher standard of living in a given area can be attributed to good human development, with a particular focus on scientific education. The study region has excellent access to roads, medical facilities, educational options, work opportunities, and so forth. Additionally, their effects on socioeconomic shifts have been noted over time. In actuality, however, the study area's low quality of life is caused by the people's low perception level, despite its proximity to a highly developed urban core.